1999
DOI: 10.1002/(sici)1097-0134(19990201)34:2<184::aid-prot4>3.0.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Homology model of Juvenile Hormone Esterase from the crop pest,Heliothis virescens

Abstract: Juvenile Hormone Esterase (JHE) plays an essential role in the development of insects since it is partially responsible for clearing juvenile hormone (JH), one of the hormones that is responsible for insect metamorphosis. JHE is a 60 kDa enzyme that selectively hydrolyzes the ␣/␤ unsaturated ester of JH. Because of its pivotal role in insect development, we have targeted JHE for use as a biopesticide. In this study, we have constructed a homology-based molecular model of JHE from the agricultural crop pest, He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…The second feature is a particular amphipathic helix. This helix was initially identified in a homology model of a lepidopteran JHE (Heliothis virescens, Thomas et al, 1999) in which basic arginine residues (R 174, 181, 185) were identified along one face. While the helix is conserved in non-JHE carboxylesterases, it is generally not amphipathic.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The second feature is a particular amphipathic helix. This helix was initially identified in a homology model of a lepidopteran JHE (Heliothis virescens, Thomas et al, 1999) in which basic arginine residues (R 174, 181, 185) were identified along one face. While the helix is conserved in non-JHE carboxylesterases, it is generally not amphipathic.…”
Section: Introductionmentioning
confidence: 88%
“…The single Jhe ortholog of all the other species each encodes a protein possessing the GQSAG motif and the amphipathic helix with three basic residues along one face that is near-universally associated with known JHEs (Thomas et al, 1999;Campbell et al, 2001). There is a frame shift mutation in D. grimshawi but this is most likely due to a sequence error since there is also a short genomic scaffold that overlaps about half of the JHE gene and it lacks the frameshift insert.…”
Section: Genomic Comparisons Among the Drosophilamentioning
confidence: 99%
“…For example, acetylcholinesterase is one of the most efficient enzymes known with rates of catalysis occurring at or near the diffusion limitation. By contrast, juvenile hormone esterase shows a k cat that is 4 orders of magnitude slower but with a higher affinity (lower K m ) for the substrate (Thomas et al, 1999). The juvenile hormone esterases have K m values ranging between 1 and 102 nM, whereas the K m value for acetylcholinesterase is about 50 M. Since juvenile hormone esterase substrates contain an extended hydrophobic acyl group and small alcohol moiety (methanol) and acetylcholinesterase requires a small acyl group for efficient catalysis, it is probably the substrate orientations in the active center of two enzymes that differ with respect to the entry portal and the position of the catalytic serine in the active center.…”
Section: ␣␤-Hydrolase-fold Proteins: a Unique Superfamily Of Proteinmentioning
confidence: 99%
“…51,52) The interaction mode of JHE with its substrate has been predicted using homology-based molecular modeling techniques. 53) The physiological significance of JHE in the regulation of JH titer has also been studied in detail. 33,35) The molecular mechanism of JH action is not clear.…”
Section: Biosynthesis Transport and Metabolism Of Juvenile Hormonementioning
confidence: 99%